2014
DOI: 10.1371/journal.pone.0093325
|View full text |Cite
|
Sign up to set email alerts
|

From Single Cells to Tissues: Interactions between the Matrix and Human Breast Cells in Real Time

Abstract: BackgroundMammary gland morphogenesis involves ductal elongation, branching, and budding. All of these processes are mediated by stroma - epithelium interactions. Biomechanical factors, such as matrix stiffness, have been established as important factors in these interactions. For example, epithelial cells fail to form normal acinar structures in vitro in 3D gels that exceed the stiffness of a normal mammary gland. Additionally, heterogeneity in the spatial distribution of acini and ducts within individual col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 38 publications
4
49
0
1
Order By: Relevance
“…For ductal elongation local collagen fibre alignment is necessitated which leads to local mechanical anisotropy in the mammary gland [17]. Provenzano et al have shown that the orientation of collagen fibres changes during tumour growth: first regions of dense collagen develop in the tissue, then the collagen fibres are aligned parallel to the tumour boundary while during further tumour growth, collagen fibres become reorganized orthogonal to the tumour boundary to enable invasion [18].…”
Section: Discussionmentioning
confidence: 99%
“…For ductal elongation local collagen fibre alignment is necessitated which leads to local mechanical anisotropy in the mammary gland [17]. Provenzano et al have shown that the orientation of collagen fibres changes during tumour growth: first regions of dense collagen develop in the tissue, then the collagen fibres are aligned parallel to the tumour boundary while during further tumour growth, collagen fibres become reorganized orthogonal to the tumour boundary to enable invasion [18].…”
Section: Discussionmentioning
confidence: 99%
“…To acquire the 3D analysis results, we calculated the θ distribution of each voxel within these 150 150 150 × × voxel stacks using the 3D vector summation technique. Regarding the 2D analysis, we calculated the θ orientation using the 2D vector summation technique in a frame-by-frame manner, which was previously reported [33]. Specifically, we applied the 2D algorithm to 150 frames of each stack sequentially, and acquired the θ orientation for every voxel of these stacks too.…”
Section: Evaluation Of the Vector Summation Technique Performancementioning
confidence: 99%
“…As a result, pixel-specific fiber orientation information can be provided faster than pixel-wise Fourier analysis with comparable accuracy by an order of magnitude. This technique has been successfully applied for studying interactions between the matrix and human breast cells [33], and mapping scar formation in histological tissue sections [34,35]. Compared to edge detection algorithms that have been developed for rapidly detecting fiber orientation in micrographs, such as algorithms based on Sobel or Canny operators [36][37][38], this technique has improved accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk mechanical properties of gels are not sufficient to explain these different morphogenetic processes because gels with collagen and 0% or 5% matrigel have very similar macroscopic mechanical properties but lead nevertheless to different epithelial shapes 10 . However, these different gels have very different microscopic properties, as shown by electron micrographs.…”
Section: Biological Modelmentioning
confidence: 99%
“…By contrast, the addition of matrigel leads to a more globular matrix, where fibers are less accessible, depending on the amount of matrigel added. 10 .…”
Section: Biological Modelmentioning
confidence: 99%